Collaborative Efforts to Education in The New Normal: Evidence Among Pantawid Pamilyang Pilipino Program (4ps) Parents in The Philippines - Glory Fe Oraller-Balazo (ELT Worldwide: Journal of English Language Teaching, 2022)
The only way to prevent COVID-19 from deepening inequality for the entire generation of children is to equip families to support learning at home. With this, the DepEd decided to have the various distance learning modalities wherein parents will now serve as front liners when it comes to supporting their children’s education. A descriptive study that aims to examine the level of awareness and readiness of Pantawid Pamilyang Pilipino Program (4Ps) parents in assisting their children’s education via distance learning modalities in the new normal was conducted. The data was collected using a survey questionnaire and were analyzed using descriptive and inferential statistics. Findings revealed a significant relationship between the awareness of (4Ps) parents on the different distance learning modalities and their preparedness to assist their children's education in the new normal. Moreover, it shows no significant relationship between the (4Ps) parents' profile in terms of their source of income and parenting status to the awareness and readiness on the various distance learning modalities.